Around-the-world flights a history - Stinson, Patrick M. (McFarland & Company, 2011)
This history of around-the-world flights explores the endeavor, starting with the first tentative journeys that allowed changing aircraft en route due to expected breakdowns. Paying tribute to the supporting personnel as well as to the flight captains at the center of attention, this work celebrates aviation's continued spirit of adventure.